15.6k views
3 votes
Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36 Given ⇒ 3(x − 4) + 5x = 9x − 36 Step 1 ⇒ 3x − 12 + 5x = 9x − 36 Step 2 ⇒ 3x + 5x − 12 = 9x − 36 Step 3 ⇒ 8x − 12 = 9x − 36 Step 4 ⇒ 8x − 8x − 12 = 9x − 8x − 36 Step 5 ⇒ 0 − 12 = x − 36 Step 6 ⇒ −12 = x − 36 Step 7 ⇒ −12 + 36 = x − 36 + 36 Step 8 ⇒ 24 = x + 0 Step 9 ⇒ 24 = x Which property yields Step 2? A) Additive Inverse Property B) Additive Identity Property C) Addition Property of Equality D) Commutative Property of Addition

User Thedz
by
5.0k points

1 Answer

0 votes

Answer:

Commutative Property of Addition

Explanation:

3(x − 4) + 5x = 9x − 36

3x − 12 + 5x = 9x − 36 Distribute

3x + 5x − 12 = 9x − 36 Commutative Property of Addition

User Sabeeh Chaudhry
by
4.8k points